Integrating corporate social responsibility criteria into executive compensation and firm innovation: International evidence - Tsang, Albert; Wang, Kun Tracy; Liu, Simeng; Yu, Li (Journal of Corporate Finance, 2021)
Using a large sample of firms from 30 countries, we find that the integration of corporate social responsibility (CSR) criteria into executive compensation is associated with greater innovation output in countries around the world. We also find that this positive association is stronger in countries with weak stakeholder orientation, countries with weak legal environments, and countries without mandatory CSR reporting requirements. These findings suggest that CSR contracting can compensate for institutional voids and high stakeholder demand for CSR, and thereby foster firm innovation. The results of the channel analyses suggest that a greater level of employee innovation productivity, enhanced managerial risk-taking, and greater responsiveness of firms' R&D investment to their investment opportunities play a significant role in the association between CSR contracting and innovation. Overall, our study demonstrates in a global context the importance of linking executive compensation to nonfinancial criteria in addition to financial criteria, and it documents the heterogeneity in the effect of CSR contracting on firm innovation in different countries.